Type A aortic dissection in patients over the age of seventy in the UK. Issue 12 (16th October 2019) - Bashir, Mohamad; Harky, Amer; Shaw, Matthew; Adams, Benjamin; Oo, Aung
Abstract: Objectives: Recent guidelines have stated that age alone should not be a limiting factor for offering life‐saving surgery to patients with acute type A dissection (ATAD). The objective of this study was to review the outcomes of patients above the age of 70 undergoing surgery for type A aortic dissection (TAAD) in the UK. Methods: Prospectively collected data of procedures undertaken on patients with an age of 70 years or more were extracted from the National Institute for Cardiovascular Outcomes Research (NICOR) National Adult Cardiac Surgery Audit registry. All operations were performed in England and Wales between 1 April 2007 and 31 March 2013. The primary outcome for this study was in‐hospital mortality. The secondary outcome was mid‐term mortality followed up to 5 years. Results: A total of 507 patients were included in the study. The highest number of procedures performed by a single surgeon during the study period was 12. The overall in‐hospital mortality rate for all ATAD patients aged 70 or over was 22.5% (114 patients); the stroke rate was 11% (57) and postop dialysis rate 15% (76). Conclusions: ATAD is a life‐threatening condition with a high mortality rate if left untreated. Our results show that surgery for ATAD in patients over 70 is feasible with acceptable mortality rates. However, similar to previous studies, rates of stroke in older patients may be higher. The present study supports the notion that age should not be a discriminating factor in operating on patients with TAAD.